Fatiguing Trunk Flexor Exercise Decreases Pain Sensitivity in Postpartum Women - Deering, Rita; Pashibin, Tatyana; Cruz, Meredith; Hunter, Sandra K.; Hoeger Bement, Marie (Frontiers in Physiology, 2019)
Background: Low back pain (LBP) is common in the general population and among postpartum women. Abdominal muscle exercise is often used to treat LBP, but it is unknown if fatiguing abdominal muscle exercise can produce exercise-induced hypoalgesia (EIH). Objectives: To assess pressure pain thresholds (PPTs) at rest and following fatiguing trunk flexor exercise (EIH) in (1) nulligravid and postpartum women to evaluate the impact of pregnancy and childbirth and (2) nulligravid women and men to examine sex differences. Methods: Seventy healthy adults (31 postpartum women, 23 nulligravid women, 16 men) participated. Postpartum and nulligravid women were tested twice (16-18 weeks apart) to identify changes in EIH with postpartum recovery. PPTs were measured at the nailbed and superior rectus abdominis before and after exercise to investigate systemic and local EIH, respectively. Rectus abdominis muscle thickness was assessed with ultrasound. Results: Postpartum women reported lower PPTs than nulligravid women at the abdomen (p<0.05) whereas postpartum women had lower PPTs at the nailbed during the first session only. Men reported higher PPTs at the nailbed (p=0.047) and similar PPTs at the abdomen compared with women (p=0.294). All groups demonstrated EIH at the abdomen (p<0.05). Systemic EIH was absent in postpartum and nulligravid women (p>0.05), while men demonstrated hyperalgesia. Local EIH was positively associated with muscle thickness for men and women, which was not significant at the second timepoint. Limitations: Acute exercise response may not reflect changes that occur with exercise training. Conclusions: Fatiguing trunk flexor exercise produced local EIH for all groups. Trunk exercises may be useful to treat abdominal pain syndromes such as those demonstrated in postpartum women who were more sensitive to pain than nulligravid women.